A Critical Review on Recent Advances in Base-Assisted Smiles Rearrangement - Kumar, K. S.; Gugulothu, Kishan; Reddy, Sabbasani R.; Venkateswarlu, Katta (Current Organic Chemistry, 2022)
Rearrangement reactions of organic substrates is a versatile and sustainable tool in the construction of complex and bioactive organics by virtue of their atom-economic, stepeconomic and waste-, time- as well as energy-minimizing attributes. The X → C (or Y) aryl rearrangement reaction through an intramolecular nucleophilic aromatic substitution is referred to as Smiles rearrangement. The Smiles rearrangement enables access to complex natural products and is a useful tool to obtain various types of compounds with diversified applications, which have undergone a potent revival in recent years. In this review, we summarize the recent reports on Smiles rearrangement and most of them require a base. A few examples of the reported base-free Smiles rearrangements were also reviewed to provide comprehensive information on the selected topic. The literature review covers the published work on Smiles rearrangement reaction since 2017. The published work in these articles include simple Smiles, Truce-Smiles, radical Smiles, Ugi-Smiles, light-assisted Smiles, Dohmori-Smiles, electrochemical Smiles and phospha-Smiles rearrangement reactions for the construction of a variety of organic compounds including acyclic, heterocyclic, carbocyclic and polycyclic compounds. The formation of organic compounds with unusual ring sizes has also been discussed in the published work. Several domono/sequential reactions were also observed in these reports involving Smiles rearrangement as a crucial step. The selected examples demonstrate the synthetic power of this approach and hence this review may be highly useful to the synthetic chemists aimed to use Smiles rearrangement in their plan.
Keywords: heterocycles